Determination of LD50 of ethyl methanesulfonate (EMS) for induction of mutations in rapeseed-mustard (Journal of Oilseed Brassica, 2026)
Mutation breeding is an effective way to enrich genetic variability in crop plants. There are two basic means, physical and chemical mutagens for inducing mutations. Among chemical mutagens, the alkylating agent, ethyl methanesulfonate (EMS) is the most commonly used mutagen in plants as it causes a high frequency of nucleotide substitutions i.e. point mutations. Hence, an optimum dose is highly desired to produce the high frequency of mutations with minimum killing of treated individuals. Therefore, the present investigation was undertaken to determine the LD50 of EMS and effect of different dosages of EMS on seed germination of two Indian mustard varieties (viz. RH-749 and NRCHB-101) and one of its important wild relative Sinapis alba. Results revealed the significant effects of EMS dosages and treatment periods on seed germination. The EMS doses (LD50) at 0.42%, 0.73% and 0.3% for duration of 12 h were found to be optimum for Indian mustard varieties (RH-749, NRCDR-101) and S. alba respectively. The LD50 of EMS for Brassica juncea was higher than the S. alba and it also varied for two varieties of B. juncea. This information would be highly useful for initiating mutation breeding programme in rapeseed-mustard crops.